2012
DOI: 10.1128/cvi.05655-11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Serum Bactericidal Antibody to Serogroup C Neisseria meningitidis in England a Decade after Vaccine Introduction

Abstract: e Serogroup C meningococcal disease incidence and carriage declined rapidly in the United Kingdom after infant serogroup C conjugate vaccination was introduced in 1999, with catch-up vaccination for children under 18 years. Antibody levels and effectiveness waned quickly in children vaccinated at 2, 3, and 4 months of age. Therefore, in 2006, the current revised schedule of doses at 3, 4, and 12 months was introduced. This study assessed age-specific protection in 2009 compared with data from historical prevac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 22 publications
2
41
0
1
Order By: Relevance
“…Ten patients aged between 12 and 82 years died. In the latter cases, the apparent vaccine failure was likely to be due to the relatively short duration of the protection induced by one vaccine dose [2]. Two of the vaccinated cases developed meningitis and two sepsis (one of them died).…”
Section: Epidemiological Featuresmentioning
confidence: 99%
“…Ten patients aged between 12 and 82 years died. In the latter cases, the apparent vaccine failure was likely to be due to the relatively short duration of the protection induced by one vaccine dose [2]. Two of the vaccinated cases developed meningitis and two sepsis (one of them died).…”
Section: Epidemiological Featuresmentioning
confidence: 99%
“…This is comparable to results from the UK reported in 2012 by Ishola et al, who found SBA titers of Ն8 in 56% of individuals 10 years after priming at an age of 10 to 17 years. Estimated vaccine coverage in the UK for this population was 60 to 88% (10). Notably, De Whalley et al recently reported SBA titers of Ն8 for over 90% of individuals 11 years after priming at a median age of 10.6 years (18).…”
Section: Discussionmentioning
confidence: 93%
“…In children aged Ͼ5 years, MenCC vaccination induced high MenC-specific antibody levels and good persistence (9)(10)(11), while MenC-specific antibody levels in infants and toddlers appeared to decline rapidly after one or multiple MenCC vaccinations (9,(12)(13)(14). Vaccination programs that include MenCC vaccination(s) only for infants and/or toddlers-like the current Dutch NIP-therefore fail to establish long-term individual protection.…”
mentioning
confidence: 97%
“…Assessment of the population levels of immunity in England to MenC, using measurements of specific functional antibody levels in age-stratified sera 10 y following MCC introduction has been performed. 11,12 Ishola and colleagues, compared the data collected in 2009 to previous seroprevalence data collected prior to vaccine introduction (1996-99) and following vaccine introduction (2000)(2001)(2002)(2003)(2004). From these data we are able to determine if the booster has had a beneficial effect.…”
Section: Seroprevalence Datamentioning
confidence: 99%
“…The UK seroprevalence data, 12 along with the antibody persistence data 10 shows that those immunised in infancy with single or multiple doses followed by a booster dose in the second year of life, do not have antibody levels which will be sufficient enough to maintain protection or herd effects until adolescence. This waning of SBA titres may adversely affect the direct protection of adolescents and also threatens the herd protection achieved by reduced nasopharyngeal carriage acquisition rates of MenC following immunisation with glycoconjugate vaccines.…”
Section: Adolescent Boostermentioning
confidence: 99%